Exposure to an androgenic agricultural pollutant does not alter metabolic rate, behaviour, or morphology of tadpoles. (15th April 2022) - Martin, Jake M.; Orford, Jack T.; Melo, Gabriela C.; Tan, Hung; Mason, Rachel T.; Ozeki, Shiho; Bertram, Michael G.; Wong, Bob B.M.; Alton, Lesley A.
Abstract: Globally, amphibian species are experiencing dramatic population declines, and many face the risk of imminent extinction. Endocrine-disrupting chemicals (EDCs) have been recognised as an underappreciated factor contributing to global amphibian declines. In this regard, the use of hormonal growth promotants in the livestock industry provides a direct pathway for EDCs to enter the environment—including the potent anabolic steroid 17β-trenbolone. Emerging evidence suggests that 17β-trenbolone can impact traits related to metabolism, somatic growth, and behaviour in non-target species. However, far less is known about possible effects of 17β-trenbolone on anuran species, particularly during early life stages. Accordingly, in the present study we investigated the effects of 28-day exposure to 17β-trenbolone (mean measured concentrations: 10 and 66 ng/L) on body size, body condition, metabolic rate, and anxiety-related behaviour of tadpoles ( Limnodynastes tasmaniensis ). Specifically, we measured rates of O2 consumption of individual tadpoles as a proxy for metabolic rate and quantified their swimming activity and their time spent in the upper half of the water column as indicators of anxiety-related behaviour. Counter to our predictions based on effects observed in other taxa, we detected no effect of 17β-trenbolone on body size, metabolic rate, or behaviour of tadpoles; although, we did detect a subtle, but statistically significant decrease in body condition at the highest 17β-trenbolone concentration. We hypothesise that 17β-trenbolone may induce taxa-specific effects on metabolic function, growth, and anxiety-related behaviour, with anurans being less sensitive to disruption than fish, and encourage further cross-taxa investigation to test this hypothesis. Graphical abstract: Image 1 Highlights: Hormonal growth promotants (HGPs) used on livestock can result in EDC contamination. 17β-trenbolone (TREN), a HPG metabolite, is widely detected in the environment. Little is known regarding the effects of TREN on early-life stages of amphibians. We test the impacts on body size/condition, metabolic rate, and behaviour of tadpoles. Intriguingly, counter to effects in fish, TREN did not affect these traits in tadpoles.